2015
DOI: 10.1007/s10973-015-4472-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermal characterization of the promising energetic material TKX-50

Abstract: The thermal behavior of dihydroxylammonium 5,5 0 -bistetrazole-1,1 0 -diolate (TKX-50) was measured by differential scanning calorimetry (DSC), thermal gravimetric analysis-Fourier transform infrared spectroscopy (TG-FTIR) and thermal gravimetric analysisdifferential scanning calorimetry-mass spectrometry (TG-DSC-MS). The critical temperature of thermal explosion (T b ) and the initial decomposition temperature (T p0 ) were determined to be 523.39 and 513.80 K, respectively. The apparent activation energy (E) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…For this purpose we have replaced the 5,5'-bistetrazole-1,10-diolate moiety by a more symmetric 5,5'-bitetrazole-1,1'-diide ion (BTEZ) and obtained relaxed scans of all possible routs of the bond breaking followed by the transition state search. As a result, we have obtained the activation energy equal 229.1 kJ mol -1 , which is rather close to the Yang's value [9]. The formation of an azide anion was found to be the most exothermic path of the BTEZ decomposition.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…For this purpose we have replaced the 5,5'-bistetrazole-1,10-diolate moiety by a more symmetric 5,5'-bitetrazole-1,1'-diide ion (BTEZ) and obtained relaxed scans of all possible routs of the bond breaking followed by the transition state search. As a result, we have obtained the activation energy equal 229.1 kJ mol -1 , which is rather close to the Yang's value [9]. The formation of an azide anion was found to be the most exothermic path of the BTEZ decomposition.…”
Section: Introductionsupporting
confidence: 82%
“…To date, a two-step process initiated by a proton transfer from hydroxylammonium cations to 5,5'-bistetrazole-1,10-diolate is generally accepted [8][9][10][11][12][13][14][15]. Early molecular dynamics studies of thermal decomposition of TKX-50 revealed that the latter decays with release of molecular nitrogen or N2O with the activation energies of 188.7 and 302.1 kJ mol -1 , respectively [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated mainly using Kissinger and Ozawa's method and the results were in different ranges depending on the test condition. [21][22][23]29 The structural stability and chemical stability of TKX-50 under high pressure and high temperature were discussed based on Raman spectroscopy results and the intermediates at high pressure were attributed to a suppression of H-transfer. 24 The structural response of TKX-50 under high pressure was studied and the experimental results showed that TKX-50 exhibits a highly anisotropic compression, with an anomalous compression of the a-axis, which was explained by the hydrogen bonds.…”
Section: 19mentioning
confidence: 99%
“…However, the thermal stability and safety of energetic material itself play crucial roles in application. Up till now, although many properties have been studied [5][6][7], the thermal decomposition, nonisothermal kinetic and safety assessment of TKX-50 have been rarely reported. Hence, in order to understand the stability and safety of TKX-50 for its application, it is extremely important to know the thermal decomposition, kinetic and safety parameters.…”
Section: Introductionmentioning
confidence: 99%